Republic of Turkey Financial Sector Assessment Program : Assessment of Observance of the CPMI - IOSCO Principles for Financial Market Infrastructures - World Bank (World Bank, Washington, DC, 2017)
The Central Bank of the Republic of Turkey (CBRT), the Capital Markets Board and the Banking Regulation and Supervisory Authority (BRSA) are the authorities with responsibility for specific elements of the Turkey National Payments System (NPS). The CBRT, is the central bank and has regulatory and oversight responsibility for payment and securities settlement systems. The CMB has responsibility for safe and efficient functioning of the capital markets and is responsible for the CSDs, CCPs and TRs. The BRSA as part of its banking supervision responsibility is responsible for regulation of payment instruments and also regulation and supervision of non-bank e-money and payment institutions. This assessment covers the following CBRT owned and operated FMIs: The Electronic Funds Transfer (EFT) system and the Electronic Securities Transfer System (ESTS). The assessment takes into account the interlinkages of the EFT and ESTS with the other FMIs in Turkey: Takasbank and MKK.